A Study on Contact Fatigue Performance of Nitrided and TiN Coated Gears. (7th November 2013) - Xu, Hongbin; Li, Hui; Hu, Jianjun; Wang, Song
Abstract : This paper discusses the effects of TiN coating on gear contact fatigue performance through contact fatigue experiment and gear rig test. The results reveal that the deposition on gears with hard coating TiN could provide the subsurface protection and improve the contact fatigue life, and the contact fatigue strength of nitrided+TiN coated 32Cr2MoV is 1557 MPa at survival probability of 99%, 284 MPa higher than that of nitrided 32Cr2MoV. Although TiN coating on the the edge of the meshing zone wore out, there is no obvious pitting at the site and the rest of meshed zone of TiN coated gear keeps well without pittings and wear grooves, which is opposite to nitrided gears with pittings and peeling off. TiN coating is dense and smooth with lower surface roughness, and it wraps up the gear tooth so that the gear surface no longer contacts with lubricant and prevents the cracks initiation, prolonging the contact fatigue life of gears.